A NEW APPROACH TO SUSTAINABLE MANAGEMENT – THE CONCEPT OF SOCIAL FARMING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The present scientific paper examines a new approach to sustainable management, related to the concept of social farming. The socio-ecological nature of the social farming makes it a valuable asset, contributing to the welfare, wellbeing, intercultural learning, labour integration and social inclusion of the most disadvantaged groups of society. The potential of the social farming for achieving sustainable development in the rural areas is enormous, including social entrepreneurship and social innovation, increased employment rates and incomes, social inclusion, training, recreation, innovation and environmental protection. Social farming, as a multifunctional model, contributes both, to the public welfare and the alternative entrepreneurial business model. The proposed systemic model represents a more comprehensive approach to the complex nature of the social faming. The results of the study encompass the theoretical review of the concept, an effective social farming model and the existing problem-solving opportunities.